2012
DOI: 10.1530/eje-11-0523
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating levels of FGF23: an adaptive response in primary hyperparathyroidism?

Abstract: Introduction: Fibroblast growth factor 23 (FGF23) and parathyroid hormone (PTH) are major players in the bone-parathyroid-kidney axis controlling phosphate homeostasis. In patients with primary hyperparathyroidism (PHPT), data on the relationship between PTH and FGF23 are scarce and not always concordant. Objective: The aim of our study was to evaluate the relationship between PTH and FGF23 in patients with PHPT and in euparathyroid patients cured after successful parathyroidectomy (PTx). Patients and methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 40 publications
(51 reference statements)
5
24
0
Order By: Relevance
“…As far as other biomarkers, our data are in line with previous studies showing that there is an elevation of FGF23 levels in patients with PHPT Our study also provided data on the FGF23 co‐receptor, Klotho, whose elevation should not be intended in correlation with kidney disease. Hence, assessing of the two molecules is not useful in the evaluation of kidney injury in PHPT.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As far as other biomarkers, our data are in line with previous studies showing that there is an elevation of FGF23 levels in patients with PHPT Our study also provided data on the FGF23 co‐receptor, Klotho, whose elevation should not be intended in correlation with kidney disease. Hence, assessing of the two molecules is not useful in the evaluation of kidney injury in PHPT.…”
Section: Discussionsupporting
confidence: 90%
“…This point opens new questions towards the elucidation of intriguing mechanisms of action of FGF23 in PHPT. Witteveen et al demonstrated that FGF23 levels are high and negatively associated with serum 1,25(OH) 2 D levels in patients with PHPT and normalize after surgery . Authors hypothesized that the increase in FGF23 represents a compensatory response to increased 1,25(OH) 2 D levels stimulated by chronic high PTH levels .…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of this observation to the pathogenesis of PHPT in humans remains uncertain. Indeed, patients with PHPT have increased levels of FGF23 in association with high serum levels of PTH, suggesting that the increased FGF23 levels might be an adaptive response to counteract increased 1,25(OH) 2 D levels as a consequence of high PTH levels 38 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…Ln-transformed FGF23 decreased significantly in both groups but the induction of iPTH by low dialysate calcium did not immediately affect FGF23 although elevated FGF23 has been reported in primary hyperparathyroidism [7].…”
Section: Discussionmentioning
confidence: 61%